Waste management practices of selected shoe manufacturers in Marikina City - Co, Maylee Franz T.
Proper waste disposal was mainly the issue of public health and sanitation in urban centers in the beginning of the twentieth century. Today, waste has become a complex problem and is now more taken as a matter of environmental sustainability. The quantities and composition of wastes that people generate on a global scale presents a major ecological concern as more waste means greater pressure on the environment?s capacity to cope with the damaging impacts of waste disposal. Thus, this study intends to know how selected shoe manufacturers in Marikina City manage their waste. It specifically aimed to identify and describe the types of wastes generated from the selected shoe factories in Marikina, determine local ordinances implemented in Marikina City related to waste management, describe the waste management system used by the selected shoe factories based on Cherimisinoff?s hierarchy of waste management (Prevention, Recycle, Treatment, Disposal), and identify areas of improvement and recommend possible solutions related to their waste management system. Data was gathered through interviews and observations with the three selected shoe manufacturers and the City of Environment Management Office. In evaluating the selected shoe factories based on Cherimisinoff?s hierarchy of waste management, the study proved that the selected shoe factories have areas of improvement. The selected shoe factories follow local ordinance of proper segregation, collection, and disposal which follow the strategies of Cherimisinoff excluding the third strategy which is the treatment. Each company has an established waste management system within them but the system they practice does not entirely maximize the recycling strategy. The researcher recommends the three selected shoe manufacturers to segregate each kind of wastes to easily know the waste volume and the recyclable materials.